Hubungan Sifat Pemakmur Masjid dengan Worldview Islam - Ghoffar, Muhammad Fathin Abdul; Mujahid, Kasori (Lembaga Yasin AlSys, 2025)
Mosques play a central role in the lives of Muslims as places of worship as well as educational, social and economic centers. This research analyzes the relationship between the prosperous nature of mosques and the Islamic worldview through a qualitative literature study. Eight main characteristics of mosque prosperity were identified, namely faith in Allah SWT, faith in the Last Day, prayer, zakat, fear of Allah, sincerity, perseverance, and patience. These qualities reflect the values ​​of monotheism, ukhuwah, and responsibility, forming a holistic Islamic worldview that includes spiritual, social, and intellectual dimensions. Mosque prosperity is an example of integrating Islamic values ​​in life, balancing relationships with Allah (habluminallah) and humans (habluminannas). This research emphasizes the important role of mosques and their prosperity in strengthening Islamic culture, forming Islamic character, and supporting a society based on an Islamic worldview, as well as being the basis for developing strategic mosque development programs.